Improving the Efficiency of the Blow-Jet WEC - Erik Villagómez-Reyes; Edgar Mendoza; Rodolfo Silva (Energies, 2023)
Establishing a renewable marine energy industry demands the development of high-efficiency devices that capture as much energy as possible. The Blow-Jet is a wave energy converter mainly composed of a sloping conical channel in the shape of a brass tube, which concentrates the waves at its widest part and expels a jet of water at its narrow upper end through an orifice that can be turbined. The device has no moving parts and great flexibility in its placement. This research presents an improvement of its geometry, increasing efficiency by minimizing undesired hydrodynamic interactions. The performance of the Blow-Jet was characterized using 3D numerical modeling and laboratory tests in a wave flume. Sixteen geometric configurations of the Blow-Jet were numerically tested, and that showing the best performance was 3D printed and assessed experimentally. The twofold objective was to evaluate the performance of the new Blow-Jet geometry and to validate a numerical tool for further geometrical improvements of the device. The novel geometry is nearly 20% more efficient than the original.